Acute exacerbations of asthma occurring frequently time to check your techniques - Bonapelli, Vijaysagar Reddy; J., Sujay D.; J., Prakruthi; S., Sathiqali A. (International Journal of Advances in Medicine, 2019)
Background: Asthmatics form a predominant section of patients in OPD. If poorly controlled the frequency of attacks requiring an emergency department visit adds to the burden. It was noticed that the patients who were on inhalational therapy had poor control despite the absence of other factors which could lead to exacerbations. Hence author evaluated the inhalational techniques. Methods: A prospective study undertaken in the department of medicine in tertiary care hospital in Dakshina Kannada District, Karnataka enlisting 25 patients admitted with acute exacerbation of bronchial asthma. The patients were assessed for their symptoms, signs and recurrent attacks along with their cough severity index and inhaler scores and the observations were tabulated. Results: Of the twenty-five, 15 were on inhalation therapy with various modes of deliveries. There were 15 males and 10 females from ages 20 to 50years. The number of attacks of asthma was higher in those not on inhalation therapies than those using inhalation therapies. Also, the level/severity of cough, measured as Cough Severity Index, was assessed among the two groups. Those on inhalation therapy had a lower grade of cough than those not on therapy . Mean AEC was 94 among those on inhalation therapy and 209 among those not on therapy. Inhalational score was calculated for each patient. There is a strong negative correlation of -0.709 between inhalation score and recurrent attacks, which is statistically significant (p=0.003). Lower inhalation scores were associated with recurrent attacks. Conclusions: Recurrent exacerbations in an asthmatic patient on inhalation therapy are due to improper inhalational technique. It was suggested that it is wise to spend time with the patients in authors OPD set up and teach them the correct techniques of using inhalational therapy hence reducing frequency of attacks and cost of health care in such patients.